Pengaruh Produksi, Konsumsi, dan Harga Kedelai Nasional terhadap Impor Kedelai di Indonesia Periode 1980 Sampai dengan 2013 - KLARA ULINA NAINGGOLAN; I DEWA GEDE AGUNG; I MADE NARKA TENAYA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Influence the Production, Consumption, and National Soybean Price Against Indonesian Soybean Imports in the Period 1980 to 2013 The type of this research is an explanatory research collaborated in quantitative approach. The data used in this research was the volume of Indonesian Soybean imports in periods of 1980 until 2013 obtained with Indonesian statistic and the Ministry of Indonesian Agriculture then the data analyzed in multiple linear regression statistical method used SPSS 20.0. The result of the study determined by the effect of production, consumption, and price which against the volume of soybean imports in Indonesia during 1980 until 2013 both effecting simultaneously and partially. National soybean production (X1), national soybean consumption (X2), and national soybean price (X3), are the independent variable in this research. Soybean production decrease the quality of imports although its consumption and national soybean price highly average, soybean consumption is a variable that has the greatest influence on the number of soybean imports during 1980 to 2013. This research concluded some suggestion to the government regarding the soybean production in order to improve the domestic production, varieties and farmer institusions. Moreover, it can be accomplished by setting the domestic soybean price to reduce different price between soybean imports and domestic soybean.